2020
DOI: 10.1212/wnl.0000000000010725
|View full text |Cite
|
Sign up to set email alerts
|

Effect of escitalopram dose and treatment duration on CSF Aβ levels in healthy older adults

Abstract: ObjectiveTo determine whether compared with placebo, treatment with escitalopram (ESC) would lower CSF (CSF) amyloid beta 42 (Aβ42) levels.RationaleSerotonin signaling suppresses Aβ42 in animal models of Alzheimer's disease (AD) and young healthy humans. In a prospective study in older adults, we examined dose and treatment duration effects of ESC.MethodsUsing lumbar punctures (LPs) to sample CSF levels before and after a course of ESC treatment, cognitively normal older adults (n = 114) were assigned to eithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…While mouse studies have suggested that the treatment with antidepressants may modulate Aβ levels or even reduce Aβ plaques, evidence in human studies is just starting to arise. In this regard, a recent prospective study has shown an overall 9.4% reduction in CSF Aβ 42 levels in cognitively normal older adults treated with shortterm longitudinal doses of escitalopram compared to those receiving placebo [75]. In addition, a study using ADNI data found that MCI subjects with a remote history of depression had a 3-year delay of progression to AD if they had been treated with selective serotonin reuptake inhibitors for more than four years [76].…”
Section: Discussionmentioning
confidence: 99%
“…While mouse studies have suggested that the treatment with antidepressants may modulate Aβ levels or even reduce Aβ plaques, evidence in human studies is just starting to arise. In this regard, a recent prospective study has shown an overall 9.4% reduction in CSF Aβ 42 levels in cognitively normal older adults treated with shortterm longitudinal doses of escitalopram compared to those receiving placebo [75]. In addition, a study using ADNI data found that MCI subjects with a remote history of depression had a 3-year delay of progression to AD if they had been treated with selective serotonin reuptake inhibitors for more than four years [76].…”
Section: Discussionmentioning
confidence: 99%
“…Studies in APP/PS1 transgenic mice showed that the SSRI citalopram caused a 50% reduction in brain amyloid plaque load, and escitalopram, citalopram's S-isomer, reduced interstitial fluid Aβ by 25% 81,82 . A controlled clinical trial of cognitively normal adults showed that escitalopram could decrease CSF Aβ42 levels in humans, with a difference of 11.1% between the control and treatment groups 83 . Our results corroborate the association of low serotonin with AD, and suggest that this effect, and potentially the benefit of serotonin modulation via SSRIs, spans all three genetic groups.…”
Section: Discussionmentioning
confidence: 99%
“…There are numerous reports that antidepressants from the SSRI group exhibit neuroprotective effects with a diverse mechanism of action. Preclinical and clinical studies indicate beneficial effects on cognitive function [ 14 , 117 , 118 , 119 , 120 , 121 , 122 , 123 ]. Furthermore, literature data indicate that SSRIs “ increase neurotrophic factors including brain-derived neurotrophic factor, promote neurogenesis in the hippocampus, and reduce levels of toxic Aβ ” [ 124 ].…”
Section: Selective Serotonin Reuptake Inhibitors (Ssri)mentioning
confidence: 99%
“…Sheline et al [ 120 ] recently published the results of a double-blind placebo-controlled clinical trial on escitalopram. The study was conducted in healthy older volunteers who were then allocated to the following groups: placebo, 20 mg escitalopram × 2 weeks, 20 mg escitalopram × 8 weeks, or 30 mg escitalopram × 8 weeks.…”
Section: Selective Serotonin Reuptake Inhibitors (Ssri)mentioning
confidence: 99%
See 1 more Smart Citation